Influence of the anodizing process variables on the acidic properties of anodic alumina films - Boldrini, Diego Emmanuel (2017)
In the present work, the effect of the different variables involved in the process of aluminum anodizing on the total surface acidity of the samples obtained was studied. Aluminum foils were treated by the electro-chemical process of anodic anodizing within the following variable ranges: concentration=1.5-2.5 M; temperature=303-323 K; voltage=10-20 V; time=30-90 min. The total acidity of the samples was characterized by two different methods: acid-base titration using Hammet indicators and potentiometric titration. The results showed that anodizing time, temperature and concentration were the main variables that determined the surface acid properties of the samples, and to a lesser extent voltage. Acidity increased with increasing concentration of the electrolytic bath, whereas the rest of the variables had the opposite effect. Theresults obtained provide a novel tool for variable selection in order to use synthetized materials as catalytic supports, adding to previous research based on the morphology of alumina layers.